PENGARUH PENYALURAN KREDIT USAHA RAKYAT (KUR), TINGKAT SUKU BUNGA TERHADAP KINERJA KEUANGAN BANK PEMBANGUNAN DAERAH MELALUI NON PERFORMING LOAN (NPL) DAN BIAYA OPERASI DAN PENDAPATAN OPERASI (BOPO) - Ratih Setyo Rini; Eko Aristanto (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2019)
People's Business Credit (KUR) is a Credit / Financing scheme specifically for Micro, Small and Medium Enterprises and Cooperatives whose businesses are feasible but do not have sufficient collateral required by the bank (unbankable). The research objective was to analyze the Effect of People's Business Credit (KUR) Distribution, Interest Rates on Financial Performance of Regional Development Banks Through Non-Performing Loans (NPL) and Operating Costs and Operating Revenues (BOPO) and analyze the differences in financial performance of Regional Development Banks before and after becoming KUR distribution Bank. The sample used in this study is the Regional Development Bank in Java, which has been incorporated in the KUR Distribution Bank in 2008, namely BPD in Yogyakarta, BPD East Java and BPD DKI Jakarta. The observation used data from the Regional Development Bank for the period 2005-2015. The results of the credit distribution and interest rates in the KUR distribution did not have a significant impact on the NPL and BOPO and showed that there were no better significant differences in the financial performance variables in the years BPD became the KUR distributor. The result recommends BPD to continue distributing KUR.